Konsep Keluarga Sakinah dalam Al-Qur'an dan Implikasinya terhadap Stabilitas Psikologis Anak: Kajian Tafsir Maudhu’i - Liwardha Simangunsong; Sahdin Hasibuan (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2026)
This study examines the concept of the sakinah family in the Qur'an and its relevance to children's psychological stability through a thematic interpretation (tafsir maudhu'i) approach. The background stems from the family's crucial role as the primary environment in shaping a child's personality and mental health, where the Qur'an emphasizes marriage as a means to achieve tranquility, affection, and generational continuity. While studies on the sakinah family abound, research specifically linking the Qur'anic concept of sakinah to children's psychological stability through a thematic approach remains limited. This study aims to analyze the meaning of sakinah in the Qur'an and explain its implications for fostering children's psychological stability within family life. Employing a library research method with a maudhu'i approach, the primary data comprises QS. Ar-Rum: 21, QS. Al-A'raf: 189, QS. Al-Furqan: 74, and QS. An-Nisa': 1, analyzed through commentaries such as Tafsir al-Mishbah, Tafsir Ibnu Katsir, and Tafsir al-Muyassar. The findings reveal that the Qur'anic concept of the sakinah family encompasses four essential elements: tranquility in the spousal relationship, love and affection within the family, spiritual education for children, and the maintenance of kinship ties. These elements significantly contribute to children's psychological stability, as a harmonious family provides the sense of security, emotional balance, and moral support essential for child development. These findings affirm that the sakinah family concept holds not only spiritual dimensions but also profound psychological relevance in cultivating mentally healthy and well-rounded individuals.